Diseño de un sistema de control y seguridad industrial para una planta empacadora de camarón - Pinos Ortega, Juan Carlos (2009)
This project involves the implementation of a Design Management System in Industrial Control and Security focuses on the analysis and risk assessment and a procedure for working at height, which aims to balance the welfare of human resources through hazard identification, risk assessment and analysis presented in the company and the prevention of incidents at work. The methodology used to achieve the objective was to perform the following activities: situational analysis of the company, a statistical analysis of accidents in the company, the risk analysis which studied the main factors in accidents, being developed for this format to record the task analysis and raised opportunities for improvement, develop a procedure for prevention and fall protection and working at heights with their respective operational guidelines and ultimately develop a computer application for the control system and safety.